Analisis Faktor Risiko Kejadian Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Miroto, Kota Semarang - Seleky, Resty Natasya; Muh, Fauzi; Martini, Martini; Lattu, Joma Chyntia (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a growing global health concern. In Semarang City, the prevalence increased from 5.97% to 6.58% between 2023 and 2024 at Miroto Public Health Center, with Miroto Subdistrict having the highest rate (6.44%). Identifying dominant risk factors is essential for targeted prevention..Methods: A cross-sectional study was conducted among 107 respondents aged ≥30 years using accidental sampling. Data were collected through structured questionnaires. The dependent variable was T2DM incidence (diagnosed by health professionals), while independent variables included age, sex, BMI, blood pressure, history of hypertension and heart disease, smoking, alcohol use, physical activity, and dietary habits. Bivariate analysis was conducted using Chi-square tests, followed by multivariate analysis using binary logistic regression. Prevalence Odds Ratios (POR) and 95% confidence intervals were reported.Result: Significant associations were found between T2DM and history of hypertension (POR=11.389), physical activity duration <30 minutes (POR=8.167), and smoking (POR=2.688). These variables remained significant in the multivariate model, indicating their dominant influence.Conclusion : Modifiable factors such as hypertension, low physical activity, and smoking are key contributors to T2DM in this urban setting. Integrated community-based interventions including hypertension screening, structured exercise programs, smoking cessation support, and dietary education should be strengthened at the primary care level. Future research should consider longitudinal approaches to better establish causality and explore sociocultural determinants.